Discusión sobre las causas del Síndrome Burnout y sus implicaciones para la salud del personal de enfermería (2012)
Objectives: To describe the causes and implications of Burnout, discussing possible consequences for the nurses. Method: This descriptive exploratory study conducted through literature review. The theme was performed by a division into categories that address the causes and factors also the implications syndrome. Results: From the analysis of the results, it appears that the process is closely related to organizational factors, personal, individual and even inherent to the profession. The effects described are numerous, involving spheres physical, mental, emotional, organizational and family. Conclusion: This is the current problem that deserves psychosocial approaches and studies that allow for measures to minimize the suffering of the working professional.